Amorphous zinc-tin oxide thin films fabricated by pulsed laser deposition at room temperature. Issue 1633 (2014) - Schlupp, P.; von Wenckstern, H.; Grundmann, M.
ABSTRACT: For a cost-efficient fabrication of homogeneous oxide thin films the usage of amorphous materials is favorable. They can be deposited at room temperature (RT) and represent an interesting alternative to amorphous silicon in electronics. Zinc-tin oxide is a promising n -type channel material for thin film transistors and consists of abundant elements, only, in contrast to the well-explored indium gallium zinc oxide. Here, the electrical and optical properties of room temperature deposited ZTO thin films are discussed. These films were fabricated via pulsed-laser deposition on glass substrates by ablating a ceramic target composed of ZnO and SnO2 in a 1:2 ratio. The resistivity has been controlled over seven orders of magnitude via the oxygen growth pressure. Further, the optical transmittance tends to be higher for higher oxygen growth pressures.